Principal instructional leadership: Implications for curriculum design, implementation, and evaluation - Muhamad Rifai; Endang Purwanti; Nurkolis Nurkolis (Universitas Pendidikan Indonesia, 2025)
This research is motivated by the challenges faced by schools in Indonesia, particularly after the COVID-19 pandemic, which requires a more flexible approach to managing the school environment and learning. The purpose of this study is to explore the instructional leadership practices of principals in creating a comfortable school environment and analyze their impact on curriculum development, implementation, and evaluation. This study employs a Systematic Literature Review (SLR) approach, analyzing relevant scientific publications from 2020 to 2024 using content analysis. The research findings indicate that the principal's instructional leadership plays a crucial role in creating a physical, psychosocial, and academic environment conducive to learning. Furthermore, this study found that effective leadership strengthens curriculum implementation, improves learning outcomes, and encourages a more comprehensive evaluation of the educational process in schools. This research makes an important contribution to the development of educational leadership policies and practices in Indonesia, particularly in the context of more holistic and responsive curriculum design, implementation, and evaluation. Abstrak Penelitian ini dilatarbelakangi oleh tantangan yang dihadapi sekolah-sekolah di Indonesia, khususnya pasca pandemi COVID-19, yang memerlukan pendekatan yang lebih fleksibel dalam pengelolaan lingkungan sekolah dan pembelajaran. Tujuan penelitian ini adalah mengeksplorasi praktik kepemimpinan instruksional kepala sekolah dalam menciptakan lingkungan sekolah yang nyaman serta menganalisis dampaknya terhadap pengembangan, implementasi, dan evaluasi kurikulum. Metode yang digunakan dalam penelitian ini adalah pendekatan Systematic Literature Review (SLR), dengan menganalisis publikasi ilmiah yang relevan dari periode 2020 hingga 2024 dengan metode analisis konten. Temuan penelitian menunjukkan bahwa kepemimpinan instruksional kepala sekolah berperan penting dalam menciptakan lingkungan fisik, psikososial, dan akademik yang kondusif untuk pembelajaran. Selain itu, penelitian ini menemukan bahwa penerapan kepemimpinan yang efektif memperkuat implementasi kurikulum, meningkatkan kualitas pembelajaran, serta mendorong evaluasi yang lebih komprehensif terhadap proses pendidikan di sekolah. Penelitian ini memberikan kontribusi penting terhadap pengembangan kebijakan dan praktik kepemimpinan pendidikan di Indonesia, khususnya dalam konteks desain, implementasi, dan evaluasi kurikulum yang lebih holistik dan responsif. Kata Kunci: iklim akademik; kepemimpinan instruksional; kepemimpinan pendidikan; lingkungan sekolah; pengembangan profesional